Prevalence of Cockroaches, Bed Bugs, and House Mice in Low-Income Housing and Evaluation of Baits for Monitoring House Mouse Infestations. Issue 3 (7th April 2022) - Abbar, Salehe; Cooper, Richard; Ranabhat, Sabita; Pan, Xiaodan; Sked, Shannon; Wang, Changlu
Abstract: Pests are frequently found in homes, especially in apartment buildings in low-income communities. We investigated the prevalence and patterns of pest infestations in low-income communities in four cities (Jersey City, Linden, Paterson, Trenton) in New Jersey, USA. Resident interviews, visual inspections, and the placement of monitors were used to identify pest infestations. A total of 1, 753 apartments from 19 buildings or building complexes were accessed. The infestation rates of cockroaches, bed bugs ( Cimex lectularius L.), and house mice ( Mus musculus domesticus Schwarz and Schwarz) were 37, 9, and 20%, respectively. Among apartments with cockroaches, 97.8, 2.5, and 0.8% had German cockroach [ Blattella germanica (L.)], American cockroach [ Periplaneta americana (L.)], and Oriental cockroach ( Blatta orientalis L.), respectively. The percentage of residents who were aware of the presence of cockroaches, bed bugs, and house mice was 70.8, 55.3, and 56.8%, respectively. The prevalence of pest infestation was associated with resident ethnicity and gender. Among 856 interview responses, 78% implemented methods themselves to control pests in their homes in the past six months. Chocolate spread detected 99% of house mouse infestations and was much more sensitive than three commercial blank baits. Significant differences were also observed in the feeding preference of the three commercial blank baits.